The Influence Mechanism of Knowledge-Based Professionals’ Core Value Identity on Creativity From the Perspective of the Knowledge Economy - Zhou, Yilin; Wang, Chunyan; Shahzad, Fakhar; Murad, Majid (Frontiers in Psychology, 2021)
In the era of the knowledge economy, tacit knowledge transfer is a key strategy for developing personal creativity, but it also is affected by core value agreement. Knowledge-based professionals have innate sensitivity with core value agreement. In the knowledge capital development system, tacit knowledge transfer is a key strategy to be discovered. This research investigates the core value identity mechanism of knowledge professionals from the perspective of the knowledge economy. The results revealed the intrinsic relationship between core values identity, tacit knowledge transferring, and personal creativity based on knowledge-based professionals’ data and employing core values identity, tacit knowledge transferring, and personal creativity based on knowledge-based professionals’ data and structural equation modeling. The results also represent the incentive path of tacit knowledge transferring in personal creativity under the core value agreement condition, which may provide a theoretical inspiration to foster knowledge-based talent creativity.